Scale of pain evaluation: perception of nurses in a neonatal intensive care unit - Xênia Martins Monfrim (Revista de Enfermagem da Universidade Federal de Santa Maria, 2015)
Aim: to identify the perceptions of nurses in relation to the use of an instrument to assess pain in preterm infants. Method: qualitative, exploratory and descriptive research conducted in a Neonatal Intensive Care Unit, in a University Hospital in Pelotas, Rio Grande do Sul. The study included four nurses, in the period of October to November 2010. Data were collected through semi-structured interviews and analyzed according to thematic analysis. Results: the following categories were addressed: Scale to assess pain in premature newborns: perception of nurses, and Pain Scale and premature newborns: implementation. Conclusion: nurses do not know the new technologies used to measure pain; however, all nurses demonstrated committment to a humanized assistance, as they reported being interested in the inclusion of this instrument of assessment